AWI-BS: An adaptive weight incentive for blockchain sharding - Zuobin Ying; Laican Song; Deng Chen; Wusong Lan; Ximeng Liu (Journal of Information and Intelligence)
The sharding technique enables blockchain to process transactions in parallel by dividing blockchain nodes into small groups, each of which handles a subset of all transactions. One of the issues with blockchain sharding is generating a large number of cross-shard transactions that need to be checked on the output shard as well as the destination shard. Our analysis suggests that the processing efficiency of cross-shard transactions is consistent with the barrel effect, i.e., that efficiency is more dependent on slower processing shard. Most of the existing studies focus on how to deal with cross-shard transactions, but neglecting the fact that the relative independence between sharding results in different incentive costs between sharding. We perform a sharding analysis on 100,000 real transactions data on Ethereum, and the results show that there is a large difference in gas prices between different shards indeed. In this paper, we propose an Adaptive Weight Incentive (AWI) for Blockchain Sharding, which uses adaptive weight in place of traditional incentive, to address the problem of differing incentive costs for each shard. Take Ethereum as an example, AWI-BS computes the weight of a transaction as a function of a combination of the underlying gas price, the latency of the transaction, and the urgency of the transaction. Then the node chooses which transaction to pack based on the AWI-BS. Lastly, we also perform an in-depth analysis of AWI-BS's security and effectiveness. The evaluation indicates that AWI-BS outperforms the other alternatives in terms of transaction confirmation latency, transaction hit rate, and system throughput.